The Influence of AI-Generated Feedback on Students’ Debate Skills in University - Daniswara, Landry Dwiyoga (JEES (Journal of English Educators Society), 2025)
The use of Artificial Intelligence (AI) tools like ChatGPT has become more common in education, especially at the university level. When it comes to learning English through debating, ChatGPT has the potential to support students by providing feedback not only on language use, but also on the content of their arguments. The purpose of this study is to investigate how using ChatGPT might impact university students’ performance in debate. The method used a mixed-method exploratory approach, combining a pre-experimental design with interviews to get a fuller picture. Eight students took part in a simulated British Parliamentary debate. They completed assessments before and after the intervention, debating two different motions which had the same topic to collect data. The finding showed that there was no improvement in students’ debate scores after using ChatGPT. The average scores were the same, 75.75, both before and after the intervention. Although there was a moderate positive correlation between pretest and posttest scores (r=0.826), the identical averages suggest that the ChatGPT tool did not have a significant effect. Interviews revealed that the students often copied the AI’s responses instead of critically engaging with the material which weakened the quality of their debate. Keywords: Artificial Intelligence, ChatGPT, debate, argument